Automatización de procesos en la industria alimentaria - Tafur Morey, Edmar Laing (2022)
This work addresses the issue of process automation in the food industry, because technological advances and quality requirements are increasingly rigorous, that is why companies today are forced to make major changes to meet the demand for products, in turn streamline production processes in large volumes. The main goal of automation is to perform work that humans cannot perform at high speed and produce large quantities in a short time, in turn reducing workloads. Automation in the food industry is a set of different technologies that go hand in hand to be able to concretize it efficiently and carry out what is planned successfully for companies. Optimization and continuous improvement methods are being a primary tool in any industrial automation process.